Cuán importante es el empleo exportador en Bolivia? - Beatriz Muriel Hernández; Alejandra Terán Orsini (Institute for Advanced Development Studies (INESAD), 2019)
– The study analyzes - direct and indirect - export employment in Bolivia, using information from both the national accounts of 2005, 2011 and 2014 and the population and housing censuses. The most important result is that the export boom, during 2005-2014, has created jobs modestly (at rates lower than the added value of the economy); given that exports have been concentrated in low labor-intensive sectors (hydrocarbons and mining). This also explains why, at the level of trading partners, MERCOSUR members accounted for 50% of total exports in 2014; but only for 11.7% of export employment.
Keywords: F14; F16; J21; 330; exports; export employment; Bolivia